Egg Yolk Fatty Acids, Blood Parameters and Some Reproductive Measurements of Japanese Quail Supplemented with Chia Seeds (Salvia hispanica L.) - Ahmed , Suad Kh. (International Journal of Poultry Science, 2019)
Background and Objective: This study was conducted to investigate the effect of supplementing Japanese quail hens with plant sources of omega-3 fatty acids on blood and reproductive traits and egg fatty acid profiles. Materials and Methods: A total of 240 female Japanese quail, 48 days old, were randomly distributed into 4 treatments with 3 replicates per treatment, as follows: T1 was the control and was without any addition and T2, T3 and T4 were supplemented with 4, 8 and 12 g chia seeds/kg diet, respectively. Results: The statistical analysis showed that T3 significantly reduced the blood uric acid, glucose, LDL, triglycerides and VLDL, while the PCV, Hb, total protein, albumin (A), globulin (G), A/G ratio, cholesterol and calcium were not affected significantly by the supplementation treatments. The egg formation hormones estrogen, follicle stimulating hormone (FSH) and luteinizing hormone (LH) increased significantly (p<0.05) in T3 compared with those in the control and other treatments, while the relative weights of ovaries and oviducts and the lengths of the oviducts did not significantly affect the egg formation hormones. The egg yolk fatty acid profiles showed significant increases in oleic, linolenic, palmitic, linoleic and stearic acids in all supplemented groups compared with those in the control. Linolenic acid increased significantly (p<0.05) in T3 and T4 compared with that in T1. Conclusion: It is concluded that the addition of chia seeds to quail diets during the laying period has a positive effect on the blood lipid profile, egg formation hormones and egg yolk fatty acid profile, especially for the more useful omega-3 fatty acids.